International Cross-Listing and the Bonding Hypothesis - SEGAL, Dan (Institutional Knowledge at Singapore Management University, 2004)
The authors describe a new view of cross-listing that links the impact on firm valuation to the firm's ability to develop an active secondary market for its shares in the U.S. markets. Contrary to previous research, cross-listing may not provide benefits for all firms, even when those firms meet the highest regulatory requirements for disclosure and supervision. When cross-listed firms are divided into two groups on the basis of their share turnover in the home market relative to the U.S. market, the firms that develop active trading in the U.S. market experience an increase in valuation. Cross-listed firms that remain predominantly traded in the home market following cross-listing are valued similarly to non-cross-listed firms. To gain the full benefits of crosslisting, a foreign firm must convince investors that their shareholder rights will be protected. The effectiveness of this reputational bonding is witnessed in the ratio of trading on the U.S. market relative to the home market.